Pengujian Black Box pada Aplikasi Absensi Karyawan Berbasis Web dengan Teknik Equivalence Partitions - Ilham Ramdhani; Risky Tuah Sinaga; Syahrul Ramadan; Wahyu Diansyah; Aries Saifudin (CV. Multi Kreasi Media, 2023)
In the application system there are some bugs or errors in the making. Therefore it is necessary to test the application so that it runs properly and checks whether a program is running properly. The application aims to evaluate whether a software is functioning as it should or there are still some program errors that must be corrected so that the quality of the software is said to be good. The methods that are used for testing include Blackbox testing which is often used by testers to study whether the program is synchronized or not. In this article the software that will be studied uses Blackbox Testing to test a web-based attendance application system at PT Sigma Cipta Utama. There are several methods in Blackbox Testing, one of which is using the Equivalence Partitions technique, which means testing based on input in each form in the Petgram mobile software, where there are the required results and the actual results together with successful or failed conclusions. Each input presentation will be tested and grouped according to its use, whether it is valid or invalid. So it is hoped that using this test is the quality of the software produced according to the expected functions, and can provide profits for the company.